Yard tractors: Their path to zero emissions. (September 2021) - Li, Chengguo; Dixit, Poornima; Welch, Bill; Nigam, Abhilash; Soriano, Bonnie; Lee, John; Russell, Robert L.; Jiang, Yu; Zhu, Hanwei; Karavalakis, Georgios; Johnson, Kent C.; Cocker III, David R.; et al.
Highlights: This paper evaluated advanced fuels and engines to lower emissions from yard tractors. Emissions of diesel yard tractors have declined with tighter emissions standards. Natural gas and LPG provide the potential for lower yard tractor emissions. Diesel water emulsions provide reductions in both PM and NOx emissions. Yard tractor emissions have declined >70% in NOx and >90% in PM at ports. Abstract: Yard tractors (YTs) are trucks used for moving trailers and containers short distances around freight terminals and port facilities, and their diesel engines contribute significantly to nitric oxide (NOx) and particulate matter (PM) emissions to a port's inventory for the cargo handling equipment (CHE) category. Over time, tougher regulations have forced the introduction of new engine and emission control technologies to reduce emissions from YTs. This paper reviews the history and emissions from a range of technologies that were introduced during the past years with the understanding that a variety of technology solutions may be used by ports worldwide to address air pollution concerns. These new technologies included: cleaner engines, new liquid and gaseous fuels (natural gas [NG] and liquified petroleum gas [LPG]), and new emission control technology. The results show how technology improvements in YT emissions control technology have led to reductions of >70% in NOx and >90% in PM in the emissions inventories for CHE at ports in Southern California.